The Relationship between Score for Allergic Rhinitis and Total Nasal Symptom Score in Individual Suspected Allergic Rhinitis - Mohd Hatimul Muqsit Zulfakri Abdullah; Ferryan Sofyan (Talenta Publisher, 2023)
Background: Allergic Rhinitis is a symptom disorder that mainly occurs in the nasal, induced after exposure to allergens and causes inflammation of the nasal mucosa mediated by Immunoglobulin E. Data quoted from the American Academy of Allergy Asthma & Immunology shows that 10-30% of the world’s population is affected by allergic rhinitis and still increasing in numbers. To screen and evaluate the severity of allergic rhinitis with ease, two questionnaires have been formed, namely Score For Allergic Rhinitis and Total Nasal Symptoms Score. Objective: To identify the relationship between Score For Allergic Rhinitis and Total Nasal Symptoms Score in individual with suspected allergic rhinitis. Methods: This study uses a descriptive analytic research method with a cross-sectional study approach. The sample individual was selected using a non-probability sampling technique, namely purposive sampling with a sample size of 95 people. Results: Using Spearman Correlation Test, a significant relationship was found (p = 0.000) and a correlation coefficient value shows (p=0.535) there is a strong relationship between these two questionnaires. Conclusion: There is a strong and positive relationship between Score For Allergic Rhinitis and Total Nasal Symptoms Score questionnaire in patients with suspected allergic rhinitis.